Peningkatan prestasi siswa PKn tentang peranan politik luar negeri indonesia melalui power point interaktif - Umi Kulsum (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2023)
The aims of this research are: 1). Describe the application of the Interactive Power Point Method to Students. 2). describes the increase in Civics learning achievement on the material Role of Indonesia's Indonesian Foreign Politics through the Interactive Power Point Method for Students. This study uses a class action research design. The material chosen in this study is the Role of Indonesian Foreign Politics while the data collection technique used is by taking the results of observations during the learning process of student learning values. The design model used refers to the Kemmis & Taggart (1988) design with cycles; Each cycle consists of 4 stages, namely: (1) preparing an action plan, (2) implementing the action, (3) observing, and (4) reflecting, drawing conclusions and suggestions. And the results of this study can be summarized as follows: 1) the dominant process skills carried out by students are conducting research, while what students do the least is formulating problems and concluding research results and 2) student learning outcomes using the Interactive Power Point learning method increase to 100, 00%.